Advances in gluten detection: A rapid colorimetric approach using core-satellite magnetic particles - Daniele Marra; Adriano Acunzo; Andrea Fulgione; Maria De Luca; Reynaldo Villalonga; Francesco Pisani; Loredana Biondi; Federico Capuano; Raffaele Velotta; Bartolomeo Della Ventura; Vincenzo Iannotti (Biosensors and Bioelectronics: X)
Monitoring gluten levels in foods labelled as gluten-free or low-gluten — i.e. containing less than 20 ppm and 100 ppm of gluten, respectively — is crucial for preventing celiac disease-related disorders. Due to their inherent complexity, the standard analytical techniques to assess the gluten content in food are not suitable for on-site measurements, whose need is widely recognized. In this context, we developed a rapid and cost-effective biosensor based on core-satellite magnetic particles (CSMPs) — magnetic cores coated with gold nanoparticles (AuNPs) — further functionalized with anti-gliadin antibodies. The study demonstrates that a 0.016% concentration of the surfactant Tween-20 can induce the spontaneous formation of stable CSMP clusters in dispersion. These clusters, composed of weakly interacting functionalized CSMPs, undergo fragmentation in the presence of gliadin, which specifically binds to the antibodies on the CSMPs. This process results in a colour change, which is measurable by a UV–VIS spectrophotometer. Gliadin extraction was achieved by treating the sample with a non-toxic ethanol-water mixture (60%), sufficient to induce a measurable colour change in the presence of gluten contamination, with a limit of detection (LOD) of 8 ppm, which is lower than low limit established for gluten-free food.